Potencjał wydobywczy złóż gubińskich ze szczególnym uwzględnieniem złoża Gubin-Zasieki-Brody = The extraction potential of lignite deposits in gubin region with special regard to Gubin-Zasieki-Brody lignite deposit - Kasztelewicz, Zbigniew; Zajączkowski, Maciej; Sikora, Mateusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The thesis presents extraction potential of lignite deposits in Gubin region which include "Gubin" and "Gubin-Zasieki-Brody" lignite deposits. Irregular recognition of a deposits has accepted. Documentation of the eastern part of deposits has been done at the least accurate recognition category "D". The new boundary of balance coal reserves in "Gubin" deposits was defined and their potential taking into account Best Available Techniques which are 1100MW power units.
Keywords: węgiel brunatny; złoże Gubin; złoże Gubin-Zasieki-Brody; zagospodarowanie złóż; lignite; Gubin lignite deposit; Gubin-Zasieki-Brody lignite deposit; utilization of deposits